Winter air pollution by and inhalation exposure to nitrated and oxygenated PAHs in rural Shanxi, north China - Du, Wei; Chen, Yuanchen; Shen, Guofeng; Wang, Wei; Zhuo, Shaojie; Huang, Ye; Pan, Xuelian; Tao, Shu (Atmospheric environment (1994), 2018)
Polar polycyclic aromatic hydrocarbons (PAHs) derivatives like nitrated and oxygenated PAHs have higher toxic potentials than the parent one, and are receiving growing interests. In this study, we investigated household air pollution and personal exposure to nitro- and oxy-PAHs during a winter period in rural Shanxi, northern China. The overall arithmetic means of 24-h average indoor nitro-PAHs and oxy-PAHs were 10.2 ± 3.6 and 76.8 ± 51.8 ng/m3, respectively, that were much higher than the 7.98 ± 4.30 and 54.7 ± 45.4 ng/m3 in the outdoor air. Nearly 90% of particulate PAHs derivatives were enriched in fine PM2.5 and even finer PM1.0 fraction. Daily inhalation exposure to nitro- and oxy-PAHs for the rural population were 8.41 ± 3.08 and 68.5 ± 79.7 ng/m3, respectively. Residents burning briquette for cooking were found to have lower household air pollution and exposure levels compared with those burning wood. The calculated time-weighted average concentration overestimated, though correlated positively, the daily inhalation exposure compared to the that from personal carried samplers. [Display omitted] •Nitrated and oxygenated PAHs in paired indoor-outdoor rural households.•Inhalation exposure to PAHs derivatives using portable samplers.•Enrichment in fine and sub-micron particle fractions.•Substantial discrepancy between the time-weighted average concentration and directly measured exposure.•Lower pollution in homes burning briquettes for cooking compared to the use of wood combustion.